2021
DOI: 10.7759/cureus.14114
|View full text |Cite
|
Sign up to set email alerts
|

Remote Clinics During Coronavirus Disease 2019: Lessons for a Sustainable Future

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has led to a focus on non-face-to-face (NF2F) orthopedic clinics. In this study, our aim was to establish whether NF2F clinics are sustainable according to the “triple bottom line” framework by taking into account the impact on patients, the planet, and the financial cost. Methodology This retrospective cohort study was carried out at a large district general hospital with 261 patients identified as having undergone fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 7 publications
(10 reference statements)
0
29
0
Order By: Relevance
“…Three main environmental issues were identified. Nine studies focused on waste management, 18,[39][40][41][42][43][44][45][46][47] three on carbon emissions, [48][49][50] and one on water usage 51 (Table I). The quality assessment of the studies is detailed in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three main environmental issues were identified. Nine studies focused on waste management, 18,[39][40][41][42][43][44][45][46][47] three on carbon emissions, [48][49][50] and one on water usage 51 (Table I). The quality assessment of the studies is detailed in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated the carbon emissions generated by orthopaedic activities (Table VI). [48][49][50] Baxter et al 48 investigated the CO 2 emissions generated by ten frequently used items across three different hand surgery procedures performed by 32 different surgeons. This study reported a range of 7.8 kg to 28.8 kg of CO 2 emissions generated through the use of these items.…”
Section: Resultsmentioning
confidence: 99%
“…The questions selected were based on previous papers by Fatehi et al [ 14 ], who assessed patient satisfaction in a remote diabetic clinic, as well as Curtis et al [ 4 ] and Graham et al [ 5 ], who assessed patient satisfaction for remote orthopaedic consultations in a secondary care setting. The questionnaire was then reviewed and adapted by one general practitioner (GP) and three patients for clarity of content and accessibility via mobile phone.…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of remote consultations in the form of text messages and telephone and video appointments has been ramped up significantly in recent years [1][2][3]. Telehealth has been shown to be a useful alternative to face-to-face appointments and has advantages for patients, health practitioners and the environment [1][2][3][4][5][6]. Today the use of remote consultations is omnipresent across medical specialities, a process greatly accelerated by the coronavirus disease 2019 (COVID-19) pandemic [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation